Free versus unfree labor: challenging their boundaries - Renard, Léa; Wobbe, Theresa (Shifting categories of work, 2022)
In this chapter, we do not consider “forced labor” as an exception to the presumably dominant “free labor” within the market system or as a relic from ancient times. Instead, we contend that coerced labor arrangements are at the very core of contemporary global economic processes. We firstly aim to understand the relationship between free and forced labor from a historical-sociological perspective by asking why conceptions of freedom in the Western world developed in a way that demarcated them from various forms of coerced labor. Secondly, we take the international regulation of coerced labor in the ILO from the interwar period onward as a case in point and explore the social and historical conditions under which “forced labor” became a category of knowledge and action for the organization. We show that negotiation of the boundary between free and unfree labor was key to the institutionalization of forced labor as a category of international labor law and statistics. In the final section, we discuss how the social sciences might blur the boundary between free and unfree labor for analytic purposes and the consequences of this analytic shift for our understanding of work past and present.
Gesehen am 05.05.2023
Erschienen 30 December 2022